Student’s experiences in using Malay language (L1) in Arabic language classroom - Ahmad Kamel, Nazihah (Institut Pendidikan Guru Kampus Ilmu Khas, 2024)
This qualitative research study sought to explore how the student responds towards the use of Malay language (L1) in Arabic language (L2) classroom. This study enriches the literature by investigating the experience of Arabic language classroom students regarding the utilization of Arabic and Malay languages in their Arabic classes. The data gathering consists of a semi-structured interview with a student selected through purposive sampling based on her extensive experience of more than ten years in learning Arabic as a second language. A qualitative approach was utilised to analyse the data. The data were analysed and coded using thematic analysis to identify overall themes and patterns throughout the data. The finding of this study yields into four parts; learning aid for explaining vocabularies, L1 use as a socialization tool, reducing anxiety and improving self-confidence, and the negative aspect of using L1. However, more research should be carried out to see if the results are similar or even if there are other uses of L1. Another option that can be considered as further research is the quantity of the use of L1 in regard to students’ level of language proficiency.